2006
DOI: 10.1063/1.2165598
|View full text |Cite
|
Sign up to set email alerts
|

Supergiant magnetoimpedance effect in a glass-coated microwire LC resonator

Abstract: Supergiant magnetoimpedance (SGMI) effect was found to be present in a LC resonator consisting of a glass-coated amorphous Co83.2B3.3Si5.9Mn7.6 microwire. It is found that the form of the impedance curves as a function of applied field is highly sensitive with increasing frequency. The phase angle was also strongly found to be dependent on this field. As one approached the resonance frequency, extremely large increments of magnetoimpedance are observed. SGMI values of 400 000% are found by precise tuning of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
5
1
1
Order By: Relevance
“…This also differs from what was observed in GMI curves relating to the ferromagnetic resonance in the high-frequency range 1-10 GHz for Co-based microwires [11,12]. In the present work, the appearance of a GMI multiple-peak feature can be determined not only by the LC-resonance circuit [5], but is also related to the formation of standing magnetic waves within the sample [4]. If this is the case [4], any change in microwire dimension can cause a change in the number of GMI peaks.…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…This also differs from what was observed in GMI curves relating to the ferromagnetic resonance in the high-frequency range 1-10 GHz for Co-based microwires [11,12]. In the present work, the appearance of a GMI multiple-peak feature can be determined not only by the LC-resonance circuit [5], but is also related to the formation of standing magnetic waves within the sample [4]. If this is the case [4], any change in microwire dimension can cause a change in the number of GMI peaks.…”
Section: Resultscontrasting
confidence: 88%
“…Both methods have proved useful for developing ultrasensitive magnetic sensors, which meet specific engineering requirements. In our recent work [5], we discovered a super-giant magnetoimpedance (SGMI) effect in a glasscoated microwire LC-resonator in which the LC-resonator was directly constructed on a glass-coated magnetic microwire by forming two capacitive terminal electrodes at the ends of the microwire without direct contact to its ferromagnetic core. The sudden changes in magnetoimpedance around the resonance frequency were observed, and the SGMI effect reached an extremely high value, 400 000%, by precisely tuning frequency around the resonance frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually when talking about improving the GMI effect, we mainly focus on the optimization of sandwich film, including the material properties and geometrical parameter such as thickness and width. Recently there are reports that the introduction of the capacitance could also increase the GMI effect [10].…”
Section: Article In Pressmentioning
confidence: 99%
“…Both methods have proved useful for developing ultrasensitive magnetic sensors that can operate at very high frequencies [71][72][73][74][75][76][77][78][79][80]. In particular, Kim et al [81] have recently demonstrated the superior features of LC filter-type magnetoimpedance sensors.…”
Section: Introductionmentioning
confidence: 97%